LMDI decomposition of energy consumption in Guangdong Province, China, based on an energy allocation diagram. (15th August 2017) - Chong, ChinHao; Liu, Pei; Ma, Linwei; Li, Zheng; Ni, Weidou; Li, Xu; Song, Shizhong
Abstract: This manuscript analyzes the influencing factors of energy consumption growth in Guangdong Province using the logarithmic mean Divisia index I (LMDI) decomposition method developed based on the physical processes of energy utilization from the primary energy supply to end-use sectors. By introducing the input-output method for mapping the energy allocation diagrams of Guangdong Province, we derive the primary energy quantity conversion factors, which establish the connection between end-use energy consumption and primary energy consumption. These factors are used to develop an LMDI decomposition method suitable for analyzing the energy consumption growth of this region. The method is subsequently applied to analyze the factors influencing energy consumption growth in Guangdong Province from 2004 to 2014. The results indicate that the growth of GDP per capita and population are the dominant factors driving energy consumption growth, while the improvement of electricity supply efficiency is the main factor inhibiting energy consumption growth. Highlights: A method to derive primary energy quantity conversion factors ( K PEQ ) based on the input-output method. Energy allocation diagrams of Guangdong Province in 2004, 2009 and 2014. An improved LMDI method to decompose regional energy consumption growth.